Perspectives for implementing fisheries certification in developing countries - Pérez-Ramírez, M.; Phillips, Bruce; Lluch-Belda, D.; Lluch-Cota, S. (Pergamon, 2012)
This paper discusses the future of the Marine Stewardship Council (MSC), a market-based certification program, in developing countries and exposes the challenges and opportunities for fish producers. The MSC needs to attract the interest of more fishing enterprises from these regions to increase its global presence. Because most fisheries in developing countries cannot meet the MSC standards, or afford the certification process costs, it is suggested that there is a need for developing different levels within the MSC system and additional third-party assessing organizations. MSC certification may mean adoption of improvements in fisheries management and approving fishing regimes in developing countries. However, post-certification benefits may decrease as more fisheries become certified.